Discrepancy of Cytogenetic Analysis in Western and Eastern Taiwan - Yu-Hsun Chang; Pui-Yi Chen; Tzu-Ying Li; Chung-Nan Yeh; Yi-Shian Li; Shao-Yin Chu; Ming-Liang Lee (Elsevier, 2013)
This study aimed at investigating the results of second-trimester amniocyte karyotyping in western and eastern Taiwan, and identifying any regional differences in the prevalence of fetal chromosomal anomalies. Methods: From 2004 to 2009, pregnant women who underwent amniocentesis in their second trimester at three hospitals in western Taiwan and at four hospitals in eastern Taiwan were included. All the cytogenetic analyses of cultured amniocytes were performed in the cytogenetics laboratory of the Genetic Counseling Center of Hualien Buddhist Tzu Chi General Hospital. We used the chi-square test, Student t test, and Mann-Whitney U test to evaluate the variants of clinical indications, amniocyte karyotyping results, and prevalence and types of chromosomal anomalies in western and eastern Taiwan. Results: During the study period, 3573 samples, 1990 (55.7%) from western Taiwan and 1583 (44.3%) from eastern Taiwan, were collected and analyzed. The main indication for amniocyte karyotyping was advanced maternal age (69.0% in western Taiwan, 67.1% in eastern Taiwan). The detection rates of chromosomal anomalies by amniocyte karyotyping in eastern Taiwan (45/1582, 2.8%) did not differ significantly from that in western Taiwan (42/1989, 2.1%) (p = 1.58). Mothers who had abnormal ultrasound findings and histories of familial hereditary diseases or chromosomal anomalies had higher detection rates of chromosomal anomalies (9.3% and 7.2%, respectively). The detection rate of autosomal anomalies was higher in eastern Taiwan (93.3% vs. 78.6%, p = 0.046), but the detection rate of sex-linked chromosomal anomalies was higher in western Taiwan (21.4% vs. 6.7%, p = 0.046). Conclusion: We demonstrated regional differences in second-trimester amniocyte karyotyping results and established a database of common chromosomal anomalies that could be useful for genetic counseling, especially in eastern Taiwan.